Temporal variation in maternal nest choice and its consequences for lizard embryos. (16th May 2020) - Pruett, Jenna E; Fargevieille, Amélie; Warner, Daniel A
Abstract: Microhabitat choice of nest sites is an important maternal effect that influences the survival and development of embryos in oviparous species. Embryos of many species display a high degree of plasticity in response to developmental environments, which places maternal nesting behavior under strong selective pressure, particularly in temporally changing environments. Nesting behavior varies widely across taxa that exhibit diverse reproductive strategies. The brown anole ( Anolis sagrei ), for example, lays one egg every 7–10 days across an extended reproductive season from April to October. This aspect of their reproduction provides an opportunity to examine temporal shifts in nesting behavior and its consequences on egg survival and offspring development under seasonally changing climatic conditions. We conducted a two-part study to quantify temporal variation in maternal nesting behavior and its effect on development of A. sagrei embryos. First, we measured nest micro-environments over the nesting season. Second, we "planted" eggs across the landscape at our field site to examine the influence of nest conditions on egg survival and hatchling phenotypes. We also incubated eggs inside chambers in the field to decouple effects of nest moisture from those of other environmental variables (e.g., temperature). Females chose nest sites with higher moisture and lower temperatures relative to what was generally available across the landscape during the nesting season. In addition, eggs exposed to relatively cool temperatures had higher hatching success, and high nest moisture increased egg survival and body condition of hatchlings. Overall, we provide evidence in the field that maternal nesting behavior facilitates offspring survival.